Pengaruh Profitabilitas, Solvabilitas, Ukuran Perusahaan, Financial Distress, dan Opini Audit Terhadap Audit Delay - Salsabila, Ravika Aisyah; Prasetya, Victor; Murdianingsih, Dian; Erfandi, Eli; Rosyadi, Noor (EconBank: Journal of Economics and Banking, 2024)
This study aims to determine and analyze the effect of Profitability, Solvency, Company Size, Financial Distress, and Audit Opinion on Audit Delay. The population in this study were all food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used was Purposive Sampling using 17 companies as samples. The technical analysis of the study used Multiple Linear Regression Analysis. The results of this study indicate that profitability, solvency and financial distress have a positive and significant effect on audit delay. The higher the profitability, the faster the company will submit reports. An auditor will need more time for a company that has a high solvency ratio so that the submission of the company's report takes longer. Likewise, companies that have a high level of Financial Distress can cause Audit Delay to be longer. The greater the company's profit, while company size and audit opinion are unable to affect audit delay.